Genetic Dissection of the Pathophysiology of Cardiovascular Risk Factors - Ahola-Olli, Ari (fi=Turun yliopisto|en=University of Turku|, 2017)
Background: Genome-wide association studies (GWAS) have uncovered a pleth- ora of biological information behind complex diseases. Findings from the GWAS and subsequent functional studies can facilitate drug development by identifying novel drug targets and predicting side-effects. Aims: This thesis investigates the ability of genome-wide data to reveal potential mechanisms and treatments for cardiovascular diseases using a gene-environment interaction study, combined use of mice and human data, and detailed molecular methods involving intermediate phenotype data. Participants and methods: This thesis is based on data from The Cardiovascular Risk Factors in Young Finns Study, the Special Turku Coronary Risk Factor In- tervention Project, and national FINRISK surveys. Results: The gene-environment design was able to identify one potential drug tar- get for lowering LDL-cholesterol levels. The effect of dietary fat on serum LDL- cholesterol was more pronounced in subjects with rs9364628-TT. Combined anal- yses of mice and human data were able to identify the melanocortin 1 receptor as a potential drug target for improving cardiovascular health. By using cytokines as detailed molecular intermediate phenotypes, we were able to identify 27 loci (17 novel) associated with concentrations of circulating cytokines. Conclusions: Combined used of animal and human data and use of detailed mo- lecular intermediate phenotypes can be efficiently used to identify drug targets. More research is needed to elucidate whether gene-environment studies can be utilized in drug discovery.

Tausta: Viimeaikaiset edistysaskeleet genetiikassa ja tietokonealalla ovat mahdol- listaneet genominlaajuisten assosiaatiotutkimusten toteuttamisen. Tutkimustulos- ten odotetaan auttavan lääkekehitystä. Tavoite: Väitöskirjatyön tavoitteena on arvioida, kuinka ihmisiin keskittyvä ge- neettinen tutkimus voisi auttaa osoittamaan uusia lääkevaikutuskohteita sydän- ja verisuonitautien ja niiden riskitekijöiden hoitamiseksi. Menetelmät: Aineistona käytetään Lasten Sepelvaltimotaudin Riskitekijät (LA- SERI) –tutkimusta, Sepelvaltimotaudin Riskitekijöiden Interventio Projekti -tutkimusta (STRIP) ja FINRISK-tutkimuksia. Tulokset: Geeni-ympäristö – interaktiotutkimuksessa havaittiin yksi lokus (PARK2), jossa sijaitseva variantti sääteli ravinnon rasvahappokoostumuksen vai- kutusta verenkierrossa vallitsevaan LDL-kolesterolikonsentraatioon. Ravinnon rasvan laadun vaikutus oli korostunut henkilöillä, joilla oli rs9364628-TT alleeli. Toisessa osatyössä hyödynnettiin kliinistä ja eläintutkimusta. Työssä voitiin osoit- taa, että MC1R-reseptorin toiminta vaikuttaa verisuoniterveyteen hiirillä ja ihmi- sillä. Kolmannessa osatyössä tunnistettiin 27 lokusta (17 uutta), jotka olivat yhtey- dessä vähintään yhteen tutkituista 41 sytokiinista tai kasvutekijästä. Tuloksia voi- daan hyödyntää kehitettäessä hoitomuotoja Crohnin tautiin, MS-tautiin, Behcetin tautiin´ja keliakiaan. Johtopäätökset: Yhdistämällä dataa kliinisistä tutkimuksista ja eläintutkimuk- sista sekä tutkimalla yksityiskohtaisia molekyylitason fenotyyppejä voidaan löytää potentiaalisia lääkevaikutuskohteita. Lisätutkimuksia tarvitaan geeni-ympäristö – interaktiotutkimusten merkityksen arvioimiseksi lääkekehityksessä.